A clinicopathological study of perianal paget disease: A single center-based cohort study and literature review - Ping-Chen Hou; Chaw-Ning Lee; Tak-Wah Wong; Tzu-Chien Hsu; Cheng-Lin Wu; Julia Yu-Yun Lee (Wolters Kluwer Medknow Publications, 2022)
Background: Perianal Paget disease (PPD), an uncommon extramammary Paget disease, is characterized by intraepidermal pagetoid spread of atypical Paget cells in the perianal skin. PPDs can be primary or secondary. Secondary PPDs have poorer prognosis due to progression of the underlying anorectal carcinoma. Objectives: We analyzed the clinicopathological features of PPDs to determine the primary versus secondary PPD. Methods: We reviewed the clinicopathological features, including evidence of underlying anorectal carcinomas, tumor immunoprofiles, treatments, and outcomes of 8 cases of PPD diagnosed in our department during 1992-2019. Results: Colonoscopy was performed in 6 cases; rectal adenocarcinoma and anal canal adenocarcinoma were detected in 2 cases each. Three patients had local recurrence(s). Based on the detection of underlying anorectal cancers and immunoprofiles, 2 cases were classified as primary (one with perianal squamous cell carcinoma), 4 secondary, and 2 inconclusive for primary or secondary PPD. The immunoprofiles were CK7(+)/CK20(−)/GCDFP-15(−)/CDX2(−) in the primary PPDs; CK7(+/−)/CK20(+)/GCDFP-15(−)/CDX2(+) in the secondary and inconclusive PPDs. Eventually, all patients with secondary PPD died of the disease; one primary PPD and one inclusive PPD cases died of unrelated causes. Conclusion: We report the clinicopathological features of 8 cases of PPD in Taiwanese and first describe differential CK7 expression in the epidermal and dermal tumor cells in 2 cases of secondary PPDs, which may provide a clue to the diagnosis of secondary PPD. Since an underlying anorectal carcinoma in PPDs may be undetectable by colonoscopy, it is essential to consider anoscopy and/or anal canal mucosal biopsy to search for an occult anorectal carcinoma.